Using Prescription Patterns in Primary Care to Derive New Quality Indicators for Childhood Community Antibiotic Prescribing. Issue 12 (December 2016) - de Bie, Sandra; Kaguelidou, Florentia; Verhamme, Katia M. C.; De Ridder, Maria; Picelli, Gino; Straus, Sabine M. J. M.; Giaquinto, Carlo; Stricker, Bruno H.; Bielicki, Julia; Sharland, Mike; Sturkenboom, Miriam C. J. M.
Abstract : Background: To describe patterns of antibiotic outpatient use in 3 European countries, including 2 new pediatric-specific quality indicators (QIs). Methods: A cohort study was conducted, 2001–2010, using electronic primary care records of 2, 196, 312 children up to 14 ( Pedianet, Italy) or 18 years ( The Health Improvement Network, United Kingdom; Integrated Primary Care Information database, The Netherlands) contributing 12, 079, 620 person-years. Prevalence rates of antibiotic prescribing per year were calculated and antibiotics accounting (drug utilization) for 90% of all antibiotic prescriptions were identified (drug utilization 90% method). The ratio between users of broad to narrow-spectrum penicillins, cephalosporins and macrolides ( B / N ratio) and 2 pediatric-specific QIs: the proportion of amoxicillin users (amoxicillin index) and the ratio between users of amoxicillin to broad-spectrum penicillins, cephalosporins and macrolides ( A / B ratio) were determined. Results: The overall annual prevalence of antibiotic prescriptions was 18.0% in the Netherlands, 36.2% in the United Kingdom and 52.0% in Italy. Use was maximal in the first years of life. The number of antibiotics accounting for the drug utilization 90% was comparable. The B/N ratio varied widely from 0.3 to 74.7. The amoxicillin index was highest in the Netherlands and the United Kingdom (50–60%), lowest in Italy (30%) and worsened over time in the United Kingdom and Italy. The A / B ratio in 2010 was 0.3 in Italy, 1.7 in the Netherlands and 5.4 in the United Kingdom. Conclusions: The patterns of antibiotic prescribing varied highly with age and country. The pediatric-specific QIs combined with the total prevalence rate of use provide a clear picture of the trends of community childhood antibiotic prescribing, allowing monitoring of the impact of policy interventions.